A gender strategy for pro-poor climate change mitigation - Edmunds, D.; Sasser J; Wollenberg, Eva Karoline (2013)
The Climate Change, Agriculture and Food Security Research Program (CCAFS) of the Consultative Group for International Agricultural Resources (CGIAR) CCAFS “seeks to overcome the threats to agriculture and food security in a changing climate, exploring new ways of helping vulnerable rural communities adjust to global changes in climate.”1 The CCAFS Gender Strategy (Ashby, et al. 2012) makes the case for gender analysis as critical to increased production, improved outcomes for poverty alleviation and increased well-being, and a fairer distribution of burdens and benefits in agriculture among women and men. This report proposes a gender strategy for climate change mitigation and the promotion of low emissions agriculture—the focus of CCAFS Theme 3: Pro-Poor Climate Change Mitigation. Specifically, we provide a strategy for assuring that mitigation efforts meet the goals of poverty alleviation and food security, and do so in ways that benefit poor women materially, personally and socially. We focus on women because of their historical and contemporary disadvantages, and recognize that benefits for women are generally broader and more durable to the extent men embrace those benefits, whether out of their own material interests or from commitments to family and community well-being. Although CCAFS has separated mitigation, adaptation, and risk management into three distinct research themes, we suggest these must be addressed in an integrated way to meet farmers’ needs. Farmers are primarily concerned with their well-being and that of their families and neighbors, rather than larger global environmental issues. Many also hold a ‘landscape-view’ of their home places in which water and energy sources, forests and grasslands, farms and fallows are all considered in relation to one another in contributing to farmers’ livelihood strategies, even though strategies for adaptation may emphasize one part of the landscape and mitigation another (Shames and Scherr, 2011). Initiatives to mitigate greenhouse gas (GHG) emissions should therefore ideally enhance and at least not harm adaptation and risk management. Similarly adaptation should aim to minimize GHG emissions where possible.